SADDLE NOSE AND WEGENER'S VASCULITIS - Neves, José Carlos (2006)
INTRODUCTION : The Soddle nose is a nasal dysfunction, which results from the lack of structural support, observed mainly in its middle third. Wegener 's vasculitis is one of the causes, but not very common. We make a review of the formation mechanism of the saddle nose , with a special attention to the resulting processes of the Wegener's vasculitis. We present 3 cases of patients with Wegener's vasculitis submitted to Rhynoplosty.PATIENTS ANO METHODS: We present 3 cases of saddle nose caused by Wegener's vasculitis. We discuss functional and aesthetic evaluation ond the surgical strategy adopted.RESULTS: The 3 patients presented saddle nose, resulting from Wegener's vasculitis. After complete remission they were submitted to a rhinoplasty of augmentation. Conservative opproaches were made (intercartilaginous incision in 1 patient and a vertical incision in the columella in 2 patients) and grafts were used (conchal cartilage in 2 patients ond Silostic® in 1 patient). Photographs of pre ond post-OP are presented.CONCLUSION: Wegener's vasculitis has specifity for the ENT territories. When it is not diagnosed early, complications may occur, such as saddle nose. lts correction is still a challenge to rhynoplasty.